Días contados - Uribe, Imanol, 1950-; Gómez, Carmelo; Madrid, Juan, 1947- (Aiete Films, S.A. : Ariane Films, S.A., 1994)
Antonio, a member of an ETA terrorist cell that is hatching a plot against Madrid, challenges his priorities when he falls in love with Charo, a beautiful drug addict 12 years younger than he.